High‐Efficiency, Vacuum‐Deposited, Small‐Molecule Organic Tandem and Triple‐Junction Photovoltaic Cells. Issue 18 (14th August 2014) - Che, Xiaozhou; Xiao, Xin; Zimmerman, Jeramy D.; Fan, Dejiu; Forrest, Stephen R.
<x xml:space="preserve">Abstract</x> High‐efficiency, vacuum‐deposited small‐molecule organic tandem and triple‐junction photovoltaic cells are demonstrated. The devices are composed of two sub‐cells with minimal absorption spectral overlap. A nearly transparent fullerene/wide‐energy gap organic mixture is introduced as the interconnecting blocking layer to further reduce cell losses. A power conversion efficiency of 10.0% is achieved for the tandem cell and 11.1% is achieved for a triple‐junction cell. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>